Removing the Australian tax exemption on healthy food adds food stress to families vulnerable to poor nutrition. (12th September 2017) - Landrigan, Timothy J.; Kerr, Deborah A.; Dhaliwal, Satvinder S.; Savage, Victoria; Pollard, Christina M.
Abstract: Objective : To assess the impact of changing the Australian Goods and Services Tax (GST) on household food stress, which occurs when >25% of disposable income needs to be spent on food. Methods : Weekly healthy meal plan costs for average‐income (AI), low‐income (LI) and welfare‐dependent (WDI) families were calculated using the 2013 Western Australian (WA) Food Access and Costs Survey. Four GST scenarios were compared: 1) status quo; 2) increasing GST to 15%; 3) expanding base to include exempt foods at 10% GST; and 4) expanding base to include exempt foods and increasing the tax to 15%. Results : Single‐parent families risk food stress regardless of their income or the GST scenario (requiring 24–42% of disposable income). The probability of food stress in Scenario 1 is 100% for WDI two‐parent families and 36% for LI earners. In Scenarios 3 and 4, food stress probability is 60–72% for two‐parent LI families and AI single‐parent families, increasing to 88–94% if residing in very remote areas. Conclusion : There is food stress risk among single‐parent, LI and WDI families, particularly those residing in very remote areas. Implications for public health : Expanding GST places an additional burden on people who are already vulnerable to poor nutrition and chronic disease due to their socioeconomic circumstances.